A Study of Student Responses in the Implementation of Simulation Learning Models in Physics Subjects - Roro Hoyi; Minarni Minarni (Schrödinger: Journal of Physics Education, 2023)
Research Objectives: This study aims to see students' responses using a simulation model while studying physics at SMAN 1 Muaro Jambi. Methodology: This type of research is Mixed Methods in quantitative methods using student response questionnaires, and qualitative methods using interview instruments. The research subjects were 29 students from one class X MIA 5. Quantitative data analysis techniques used descriptive statistics. Main Findings: The results of the analysis obtained from student responses using simulation models in physics subjects, namely, have a good response in using simulation models. Novelty/Original Research: Choosing a good learning model will affect students' attitudes during class hours, if the learning model makes students enthusiastically active, the learning process will be productive. In the physics subject, students' responses using the direct instruction model can be said that students do not understand the concepts and formulas described by the teacher.